AGRICULTURE OF KARAKALPAKSTAN (1960-1990- Years) (American Journal of Technology and Applied Sciences, 2022)
The article talks about the agriculture of Karakalpakstan in the 1960s-1990s. From the middle of the 20th century, political and economic changes in the agrarian sector, business plans in the rural household sector and their implementation have been reported. The introduction of new technologies in the field of population economy, the advancements in the agricultural sector, and the livelihoods of rural workers are included.